Folktales as a media for positive character building education in elementary schools (Case Study in Karawang, West Java, Indonesia) - Prawiyogi, Anggy Giri; Suparman, Tarpan; Fitri, Ayu (Edelweiss Applied Science and Technology, 2025)
The integration of literature into educational curricula has been recognized as a vital component in fostering positive character traits among students. However, many elementary schools in Indonesia have not fully utilized literature as a pedagogical tool, leading to a lack of awareness regarding the application of positive values in daily life. This study aims to investigate the impact of literature learning on the development of positive character traits in elementary school children, identify specific character traits that can be enhanced through literature, and propose effective teaching methods for literature that support character development. A qualitative case study approach was employed, involving three public elementary schools in Karawang. Data were collected through observations, interviews, and thematic analysis to explore the relationship between literature learning and character development. The findings indicate that literature learning significantly contributes to the enhancement of positive character traits such as empathy, honesty, and social responsibility. The study highlights the effectiveness of using local literary works, such as folklore, to engage students and promote moral values. This research underscores the importance of integrating literature into the educational curriculum as a means of character education. By emphasizing the values embedded in literary texts, educators can foster not only academic skills but also the moral and social development of students, ultimately contributing to the formation of a more character-driven younger generation.